PASANG SURUT PENGHULU SEBAGAI ABDI NDALEM DI KASUNANAN SURAKARTA 1931-1937 M - Wisnu Fachrudin Sumarno; Miftahul Khoiri; Ulum Fasih (Batuthah: Jurnal Sejarah Padaban Islam, 2023)
Penghulu is a servant in the religious aspect in the Surakarta Sunanate in particular and in the Archipelago in general. He is someone who serves as a spiritual figure in Kasunanan. Penghulu is interesting to review, considering that currently it is not highly valued. This research on the prince uses the historical method with four stages of research, namely, first, searching for documents, second, criticizing documents, third, carrying out interpretations or interpretations, and fourth, presenting them in written form. In this research it can be concluded that, a penghulu is needed to receive education, which in the process of education in Kasunanan Surakarta is arranged through two madrasah levels, namely, first Madrasah Waran Hoeparanta (Voorbereidende-Afdeeling) which is divided into two parts and taken for 5 years with a minimum age of 15 years. Meanwhile, the second is the Wara Krida-Reh-Wara (Vak-Afdeeling) Madrasah which is taken for 4 years with the condition that students are not yet 25 years old. The penghulu who is part of the Ndalem servant of the Kasunanan Surakarta has two positions, namely, first, the servant of the master of the suranata, who is in charge of reciting prayers and tahlil, as well as serving as porters of port goods and serving incense. Second, Abdi ndalem ngulama anon-anon, who has the task of welcoming the Kasunanan tradition, assisting in the implementation of marriages of the sons and daughters of the ndalem, and as an instructor of Islam in the Surakarta Sunanate. As a royal servant in the Kasunanan Surakarta. The life of the prince is paid by the Surakarta Sunanate. The prince has high charisma, because apart from being a courtier, he is also a role model in the religious aspects of the Kasunanan community and public society, so that in his life, the prince deserves to have a decent and guaranteed life.